2023
DOI: 10.15252/embj.2022112198
|View full text |Cite
|
Sign up to set email alerts
|

NALCN‐mediated sodium influx confers metastatic prostate cancer cell invasiveness

Abstract: There is growing evidence that ion channels are critically involved in cancer cell invasiveness and metastasis. However, the molecular mechanisms of ion signaling promoting cancer behavior are poorly understood and the complexity of the underlying remodeling during metastasis remains to be explored. Here, using a variety of in vitro and in vivo techniques, we show that metastatic prostate cancer cells acquire a specific Na + /Ca 2+ signature required for persistent invasion. We identify the Na + leak channel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Additionally, it has been shown that NALCN expression is altered in several cancer types (reviewed in Cochet‐Bissuel et al , 2014 ). In this study, Folcher et al ( 2023 ) observed an upregulation of NALCN in prostate cancer and associated metastatic tumor tissues compared with normal prostate tissues, and this correlated with the expression of Src, a tyrosine kinase that stimulates cancer invasion by interacting with matrix metalloproteinases and several proteins associated with cancer cell aggressive behavior. NALCN downregulation further suppressed invadopodia formation and abolished prostate cancer cell invasion but not proliferation.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Additionally, it has been shown that NALCN expression is altered in several cancer types (reviewed in Cochet‐Bissuel et al , 2014 ). In this study, Folcher et al ( 2023 ) observed an upregulation of NALCN in prostate cancer and associated metastatic tumor tissues compared with normal prostate tissues, and this correlated with the expression of Src, a tyrosine kinase that stimulates cancer invasion by interacting with matrix metalloproteinases and several proteins associated with cancer cell aggressive behavior. NALCN downregulation further suppressed invadopodia formation and abolished prostate cancer cell invasion but not proliferation.…”
supporting
confidence: 54%
“…The authors further demonstrated that cytosolic Ca 2+ oscillations were decreased upon NALCN downregulation as well as upon the reduction of extracellular Na + concentration, proving that Ca 2+ fluctuations are dependent on continuous Na + flow. Moreover, Folcher et al ( 2023 ) showed that NALCN‐silenced prostate cancer cells display reduced SOCE and, naturally, diminished Na + flow, making the connection between NALCN‐mediated Na + influx and cytosolic Ca 2+ levels. They propose a mechanism for the maintenance of cytosolic Ca 2+ oscillations based on the positive feedback between NALCN and the reverse Na + /Ca 2+ exchanger.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have suggested NALCN may contribute to proliferation. The first found that overexpression of NALCN increases Ca 2+ oscillations in prostate cancer promoting invasion and metastasis (Folcher et al, 2023) In contrast, Rahrmann et. al, found that loss of NALCN increased the growth of gastric cancer spheroids in vitro and cell shedding and metastasis in vivo (Rahrmann et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The chloride channel CFTR and voltage-gated potassium channel KCNQ1 were described as tumor suppressors in gastrointestinal cancers (Rapetti-Mauss et al, 2017 ; Than et al, 2014 , 2016 ; Yamada et al, 2018 ). Recently, the sodium leak channel NALCN was identified as a regulator of gastric, pancreatic, and prostate cancer dissemination (Folcher et al, 2023 ; Rahrmann et al, 2022 ). In brain cancer, we found that potassium channel EAG2 and chloride intracellular channel CLIC1 promote medulloblastoma growth by regulating cell volume-gated mitosis (Francisco et al, 2020 ; Huang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%